Method for determination of electromagnetic parameters of submersible induction motors - V. V. Anikin; R. N. Khamitov (Омский научный вестник)
Positive and energy saving frequency control of submersible asynchronous electric motors demands a research of its work as a part of electrotechnical complexes of installations of electrocentrifugal pumps on the basis of modeling. This approach is oriented to development of ways of identification of parameters of its equivalent circuits on experimental data. A research objective is development of a way for determination of parameters of the equivalent circuit of submersible asynchronous electric motors with the use of integral of an attenuation curve of current of a winding of the stator without additional transition to frequency responses. The research of a way is conducted on the basis of the developed installation for identification of parameters of equivalent circuits of submersible asynchronous electric motors. For assessment of reliability of a way and a technique of identification of parameters of the equivalent circuit of the submersible electric motor with integrated conversion of an attenuation curve of current of the stator of the submersible electric motor the experiment which shows the greatest discrepancy between values of parameters of the equivalent circuit — no more than 10 % is made. The developed way of identification of parameters of equivalent circuits of the submersible postrepair electric motor, thus, allows to determine operational parameters and characteristics of the electric motor in conditions of repair service enterprises.